Leisure vehicle rental behaviour of generations X and Y in South Africa - Mahlutshana, Nomawethu (My University, 2018)
Understanding consumer behaviour, and the consumer decision-making process, allows Marketing Centres of Excellence in organisations to journey through the mind of the consumer with the intention of understanding how they arrive at their purchasing decisions. This assists marketing teams to conceptualise strategies which can deliver strong brands that will connect with the targeted consumers. It also lays a strong foundation for a brand and places it in a position where it can gain a competitive advantage and achieve market leadership. Based on the Engel-Kollat-Blackwell model of the consumer decision making process, this study investigates the differences and/or similarities in the consumer decision making process, amongst South Africa’s Generations X and Y, when making a decision to rent a car for leisure purposes. The aim is to contribute to the limited theoretical work available on consumer behaviour in the car rental industry and establish how car rental companies could apply the insights gained in their marketing strategies to attain or maintain leadership by offering packages that would resonate with and be relevant to the South African Generations X and Y. A quantitative research strategy was employed, using a survey as a data collection instrument. The survey was sent to respondents via email and data was collected from 189 respondents and after certain exclusions, a total of 96 responses from Generation X and Y respondents were analysed The study reveals that when renting a car for leisure purpose, the South African Generation X and Y do not differ significantly in need recognition, pre-purchase search, purchase decision and post-purchase evaluation. The study however finds that there is a significant difference in one criterion of the process of evaluation of alternatives amongst the two Generations under the spotlight, as consumers in Generation Y are more likely to make the final decision to rent based on what they would have experienced or what other people say about the car rental company’s service, compared to consumers in Generation X. The study confirms that consumers do recognise the need for a car when on holiday and most importantly for the car rental industry, they recognise the need for renting it. Even though the difference in the consumer decision making process between the two generations under analysis is in only one element, the study proposes various ways in which Marketing Centres of Excellence in the car rental industry can use the insights gained to strengthen their brands and improve their market position.
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2018